THE IMPACT OF CHARACTER QUOTES STRATEGY ON EFL LEARNERS’ READING COMPREHENSION OF NARRATIVE TEXTS - Harahap, Nurlela; Safitri, Loli; Irwandi; Reflinda (ELP (Journal of English Language Pedagogy), 2025)
Many students in SMAN 8 Mandau faced difficulties in reading comprehension, particularly in identifying main ideas, locating specific information, and making inferences. Conventional teacher-centered methods, which relied heavily on explanation, limited student engagement and comprehension. To address this issue, this study investigated the effectiveness of the character quotes strategy in enhancing reading comprehension of narrative texts. A true-experimental design was employed with 11th-grade students (n = 395) across 11 classes. The experimental group received instruction using the character quotes strategy, while the control group was taught conventionally. A multiple-choice reading comprehension test served as the research instrument, and non-parametric tests (Wilcoxon Signed-Rank and Mann–Whitney U) were applied due to the data distribution. The findings revealed significant differences between the groups (Sig. [2-tailed] = 0.000 < 0.05), with the experimental group achieving higher post-test scores. These results suggest that integrating the character quotes strategy into reading instruction can significantly improve comprehension and foster greater learner engagement. The study highlights the pedagogical value of interactive strategies in EFL classrooms and provides implications for enhancing reading instruction in similar contexts.